2003
DOI: 10.1007/s00261-003-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperitoneum complicating snake bite: rare CT features

Abstract: Russels's viper bite victims with systemic poisoning may present with hemorrhagic manifestations, including spontaneous bleeding and incoagulable blood associated with disseminated intravascular coagulation and primary fibrinolysis, two of the most prominent manifestations of the systemic envenoming by this species. Various vascular complications of viperine snake bite have been reported in the literature. We report the computed tomographic findings in a case of snake bite resulting in hemoperitoneum, which, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Two cases of spontaneous hemoperitoneum with active bleeding caused by coagulopathy have been reported after a snakebite. Rathod et al 3 reported hemoperitoneum caused by intramural hematoma of the alimentary tract with active bleeding after snakebite by Russell’s viper. Ahn et al 4 also reported nontraumatic hemoperitoneum caused by hepatic necrosis and rupture after a snakebite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two cases of spontaneous hemoperitoneum with active bleeding caused by coagulopathy have been reported after a snakebite. Rathod et al 3 reported hemoperitoneum caused by intramural hematoma of the alimentary tract with active bleeding after snakebite by Russell’s viper. Ahn et al 4 also reported nontraumatic hemoperitoneum caused by hepatic necrosis and rupture after a snakebite.…”
Section: Discussionmentioning
confidence: 99%
“…2 Among these complications, coagulopathy causing spontaneous hemoperitoneum is an infrequent manifestation in snakebite victims. 3,4 Here, we report a case of a snakebite resulting in hemoperitoneum caused by spontaneous splenic rupture with active bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…A case of viperine bite causing intramural haematoma of the bowel wall with active contrast extravasation and haemoperitoneum has also been reported. 5 Viper bite resulting in haemoperitoneum caused by hepatic rupture and necrosis with active bleeding has also been reported from Korea, 6 and Uberoi reported the development of hypopituitarism due to thrombosis of the local venules leading to pituitary infarct due to DIC. 7 Multiple haemorrhagic brain infarcts have also been reported in a 65-year-old woman after envenomation by a viper bite.…”
Section: Discussionmentioning
confidence: 93%
“…On other hand in Brazil Amazon, systemic bleeding was observed during hospitalization only in 15.3% lanceheads Bothrops snakebite patients with VICC, no hemoperitoneum included (Oliveira et al, 2019). Hemoperitoneum accompanying VICC is described rather sporadically (Rathod et al, 2003;Ahn et al, 2007;Diallo et al, 2019). Splenic rupture is then very rare complication (Kang et al, 2014;Lal et al, 2014).…”
Section: Discussionmentioning
confidence: 98%